Locations of chromosomal proteins in polytene chromosomes. - Alfageme, C R (1976)
D1, a nonhistone chromosomal protein rich in both basic and acidic amino acids, has been localized at a limited number of specific loci in polytene chromosomes of Drosophila melanogaster. H2B, a nucleosomal histone, and H1, a nonnucleosomal histone, are both found throughout most chromosomal regions.